UPAYA GURU DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Abdullah Qothub, (UNISAN JURNAL, 2024)
The point of this exploration is to figure out how educators put forth attempts to expand understudies' learning inspiration in class VII Fiqh subjects at the Indonesian Unfamiliar School. The information assortment strategy in this examination utilizes a few techniques, in particular: (1) perception strategy, (2) interview technique and (3) documentation strategy. In view of the conversation of the past part, the creator can reach the accompanying determinations: the endeavors made by educators to expand the learning inspiration of class 9 understudies in fiqh subjects at Indonesian Abroad Schools are as per the following: giving acclaim, giving awards, giving tests, and giving discipline. Furthermore, inspiration to learn has three markers, specifically the endlessly want to succeed, the drive and have to learn, and expectations and goals for what's to come.